An evaluation of the 'weekend effect' in patients admitted with metastatic prostate cancer. (4th June 2015) - Schmid, Marianne; Ghani, Khurshid R.; Choueiri, Toni K.; Sood, Akshay; Kapoor, Victor; Abdollah, Firas; Chun, Felix K.; Leow, Jeffrey J.; Olugbade, Kola; Sammon, Jesse D.; Menon, Mani; Kibel, Adam S.; et al.
Abstract : Objectives: To investigate whether mortality is increased for patients with metastatic prostate cancer (mCaP) admitted over the weekend. Patients and Methods: Using the Nationwide Inpatient Sample (NIS) between 1998 and 2009, admitted patients with a diagnosis of prostate cancer and concomitant metastases were identified. Rates of in‐hospital mortality, complications, use of imaging and procedures were assessed. Adjusted logistic regression models examined associations of mortality and complications. Results: A weighted sample of 534 011 patients with mCaP was identified, including 81.7% weekday and 18.3% weekend admissions. Of these, 8.6% died after a weekday vs 10.9% after a weekend admission ( P < 0.001). Patients admitted over the weekend were more likely to be treated at rural (17.8% vs 15.7%), non‐teaching (57.6% vs 53.7%) and low‐volume hospitals (53.4% vs 49.4%) (all P < 0.001) compared with weekday admissions. They presented higher rates of organ failure (25.2% vs 21.3%), and were less likely to undergo an interventional procedure (10.6% vs 11.4%) (all P < 0.001). More patients admitted over the weekend had pneumonia (12.2% vs 8.8%), pyelonephritis (18.3% vs 14.1%) and sepsis (4.5% vs. 3.5%) (all P < 0.001). In multivariate analysis, weekend admission was associated with an increased likelihood of complications (odds ratio [OR] 1.15, 95% confidence Interval [CI] 1.11–1.19) and mortality (OR 1.20, 95% CI 1.14–1.27). Conclusion: In patients with mCaP weekend admissions are associated with a significant increase in mortality and morbidity. Our findings suggest that weekend patients may present with more acute medical issues; alternatively, the quality of care over the weekend may be inferior.